Turystyka na obszarach chronionych euroregionu Bug po przystąpieniu Polski do Unii Europejskiej na przykładzie gmin Józefów i Strzyżewice - Jeleń, Bogusław (Tourism on the Protected Areas of Bug Euroregion after the Accession of Poland to the European Union (on the Example of Jozefow and Strzyżewice Districts), 2005)
In Poland 48% of the area has tourist-holiday virtue and about 1/3 commune one. For this reason there are special possibilities of tourist development. The tourist holiday area are concentrated in Poland around borders. In the 90s euroregions came into being. They use not only their own assets but also auxilary EU assets. Thanks to vicinity of national park and landscape, Józefów and Strzyżowice commune include protected areas, which are characterized by specific nature condition. These areas are especially attractive for naturalists-scientists and for tourists. That is why there is a need to make rationalization of existing tourist base because of local and regional needs as well as for strengthening contact with a near commune.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 366-370